(untitled) (Journal of Universal Science Research, 2025)
Beekeeping has emerged as an important economic activity for many communities worldwide, contributing to the increase in income for populations. The practice provides multiple benefits, including honey production, the pollination of crops, and the production of by-products like beeswax, propolis, and royal jelly.